Speaking to reconciliation: voices of faith addressing racial and cultural divides - Hatch, John B. (Speaking of religion, 2020)
Part I: Commending, framing, and explaining the work of reconciliation -- Part II: Pursuing reconciliation through apology, forgiveness, and reparation -- Conclusion: the ongoing work of reconciliation.